New Horizons for Asian Museums and Museology - Sonoda, Naoko (Cham Springer Nature, 2016)
Cultural Heritage; Achaeology
English
Keywords: Archaeology; Social & cultural anthropology, ethnography; Cultural Heritage; Achaeology